Haplotype-based interaction of the PPARGC1A and UCP1 genes is associated with impaired fasting glucose or type 2 diabetes mellitus. Issue 23 (June 2017) - Pei, Xiaoting; Liu, Li; Cai, Jialin; Wei, Wenkai; Shen, Yan; Wang, Yaxuan; Chen, Yanzi; Sun, Panpan; Imam, Mustapha Umar; Ping, Zhiguang; Fu, Xiaoli
Abstract : Abstract: The aim of this study is to evaluate the effect of single-nucleotide polymorphisms (SNPs) of the PPARGC1A and UCP1 genes on impaired fasting glucose (IFG) or type 2 diabetes mellitus (T2DM) and the haplotype-based interaction between these genes. A cross-sectional study was conducted by cluster sampling in Henan province, China. Based on the level of fasting plasma glucose (FPG) and the history of T2DM, the participants were divided into 2 groups; 83 individuals were in the IFG+DM group (those with IFG or T2DM) and 445 individuals were in the NFPG group (those with normal FPG). Kernel canonical correlation analysis (KCCA), a haplotype-based gene-gene interaction method, which can increase the biological interpretability and extract nonlinear characteristics of SNPs, was used to analyze the correlation and interaction between PPARGC1A and UCP1 genes. The age, BMI, total cholesterol and triglycerides were statistically different between 2 groups ( P ⩽ .001). Haplotype analysis showed no significant difference in frequency distribution between the 2 groups when the PPARGC1A or UCP1 gene was tested ( P  > .05). KCCA analysis showed that the maximum kernel canonical correlation coefficient of the PPARGC1A and UCP1 genes was 0.9977 and 0.9995 in the IFG+DM and NPFG groups, respectively. A haplotype-based gene–gene interaction was observed significantly ( U  = −6.28, P  < .001), indicating the possibility of an interaction between haplotype AAG of the PPARGC1A gene and haplotypes CTCG (odds ratio [OR] = 1.745, 95% confidence interval [95% CI] 1.069–2.847) and CTCA (OR = 0.239, 95% CI 0.060–0.958) of the UCP1 gene. Haplotype-based interaction between the PPARGC1A and UCP1 genes is associated with IFG or T2DM among residents in Henan, China.